Chapter San Miniato al Monte in età moderna: spiritualità, devozione, pubblica utilità e autorappresentazione borghese - Sartoni, Enrico (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2021)
The essay analyzes the identity changes that the religious complex of San Miniato al Monte experienced in the modern age, covering both the civil plot that leads the place back to a symbol of the struggles for Risorgimento freedoms, and the spiritual and religious one. Through the transformations from monastery to fortress and then into a public utility shelter, the reconstruction investigates the new presence of the Jesuits, the conversion into a home for spiritual exercises and the new related devotional practices.